Age, Gender and Health History Factors on Blood Glucose and Uric Acid Levels in Lamongan Square Visitors - Setiyowati, Putri Ayu Ika; Syaputra, Angella Ananda; Musyarofah, Badriyatul; Fitri, Lailatus; Savitri, Nynda Ayu Nadira; Syafiq, Aji Naufal (Indonesian Journal of Engineering, Science and Technology, 2024)
Non-communicable diseases (NCDs) are health problems faced locally, nationally and globally. The metabolic keys in controlling NCDs are the control of blood pressure, blood glucose and uric acid levels. All three, play a role in the occurrence of cardiocerebrovascular diseases such as coronary heart disease and ischemic stroke which are the cause of death worldwide. NCD control starts with early detection of blood glucose, and uric acid levels. The purpose of this study was to analyze the relationship of age and medical history with glucose and uric acid levels while providing health information to the Lamongan community about blood glucose and uric acid levels. The blood of respondents over 35 years old was drawn according to consent to check both indicators with an easy touch device meter. The screening results found that most Lamongan people had normal blood sugar levels (78%), and normal uric acid in both men and women respondents (95.5% vs 96.8%). This screening activity ran smoothly and received a good response.   Keywords⎯ NCDs, Age, Medical history, Blood Sugar, and Uric Acid